1991
DOI: 10.1093/ageing/20.1.16
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Age with Aspirin Esterase Activity in Human Liver

Abstract: The activity of the phase 1 enzyme aspirin esterase was studied in liver tissue from 16 patients, aged 45-88 years. No correlation between age and enzyme activity was found in post-mitochondrial, cytosolic and microsomal fractions. These results provide further evidence that age is not a major determinant of the activity of hepatic drug-metabolizing enzymes in man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…We have measured the activity of another phase I enzyme, aspirin esterase, in normal liver tissue from patients aged 45 to 88 years (Yelland et al 1991). No correlation between age and enzyme ac-249 tivity was seen in 10 OOOg supernatant, 100000g supernatant and microsomal fractions.…”
Section: Esterasesmentioning
confidence: 96%
“…We have measured the activity of another phase I enzyme, aspirin esterase, in normal liver tissue from patients aged 45 to 88 years (Yelland et al 1991). No correlation between age and enzyme ac-249 tivity was seen in 10 OOOg supernatant, 100000g supernatant and microsomal fractions.…”
Section: Esterasesmentioning
confidence: 96%
“…Esterases, a phase 1 enzyme class mainly located in liver, plasma and specific organs such as the brain, have been studied by the Cardiff Group. These studies have demonstrated that frailty is associated with a decline in metabolic activity of plasma aspirin esterase [37–39].…”
Section: Frailty Esterases and Ageingmentioning
confidence: 99%
“…The levels of P450IIIA enzymes in women of all ages were 24% higher than in men)92] No significant age or gender effect was found in the level of human liver monooxygenases [93] or aspirin (acetylsalicylic acid) esterase in human biopsies. [94] Macrophage drug metabolising enzymes were studied in humans, based on rodent data showing a close correlation with liver levels. There was no difference in the concentration of aryl hydroxylase in 75-versus 24-year-old people, but smoking history was associated with increased levels at all ages)95] Recent reviews have emphasised that reduced phase I microsome activity is found in frail and malnourished elderly but not in the healthy community dwelling group)96] An examination of liver xanthine oxidase activity in 189 samples found no relationship with age) 97] Phase II reactants have also been studied in humans.…”
Section: Changes In Biotransformationmentioning
confidence: 99%